The EMDR Recent Birth Trauma Protocol: a pilot randomised clinical trial after traumatic childbirth. Issue 7 (2nd July 2020) - Chiorino, Valentina; Cattaneo, Maria Caterina; Macchi, Elena A.; Salerno, Roberta; Roveraro, Sara; Bertolucci, Giorgia G.; Mosca, Fabio; Fumagalli, Monica; Cortinovis, Ivan; Carletto, Sara; Fernandez, Isabel
Abstract: Objective: This pilot study investigated the effectiveness of brief EMDR intervention as compared to treatment-as-usual (TAU) in women with post-partum PTSD symptoms. Design: A pilot randomised controlled trial was conducted to evaluate possible differences between one EMDR session ( n  = 19) and one TAU session ( n  = 18) delivered in a maternity ward in the aftermath of childbirth. Main Outcome Measures: The primary outcome measure was the rate of remission of post-partum post-traumatic stress symptoms (i.e. IES-R score <23) in both groups at 6-weeks (T1) and 12-weeks' post-partum (T2). Secondary outcome measures were mother-to-infant bonding, post-partum depressive symptoms, the presence of flashbacks and level of distress. Results: Most of the women improved their post-partum post-traumatic stress symptoms after only one treatment session. EMDR resulted more effective than TAU in reducing the proportion of women with post-partum post-traumatic stress symptoms at 6-weeks' post-partum (78.9% EMDR vs. 39.9% TAU; p = .020). Moreover, women treated with EMDR experienced less flashbacks and distress as compared to TAU. No significant difference was found between treatments on mother-to-infant bonding and post-partum depressive symptoms. Conclusions: These findings, although preliminary, suggest that a brief EMDR intervention could be a viable and promising tool in the early treatment of post-traumatic stress related to traumatic childbirth.